Impacts of Postfire Management Are Unjustified in Spotted Owl Habitat - Hanson, Chad T.; Chi, Tonja Y. (Frontiers in Ecology and Evolution, 2021)
ABSTRACT: In mixed-conifer forests inhabited by California spotted owls, land managers hypothesize that without human intervention natural conifer regeneration will take many decades or longer to begin within interior areas of large high-severity fire patches, due to long distances from live tree seed sources. As a result, widespread post-fire logging, followed by sprayed application of herbicides and planting of conifer seedlings, are used to create tree plantations. These are activities routinely conducted in spotted owl territories following fires, despite current data that indicate this approach has adverse impacts on spotted owl occupancy. Land managers acknowledge such impacts, but continue these forest management practices, assuming they are a necessary harm, one that is warranted to ensure the later return of mature conifer forests used by spotted owls for nesting and roosting. However, few data have been gathered to test this hypothesis. At five years post-fire, we surveyed field plots on a grid within large high-severity fire patches in spotted owl habitat within the Rim fire of 2013 in the Sierra Nevada, California. In our analysis the percentage of plots lacking conifer regeneration decreased significantly with larger plot sizes, a finding contrary to previous studies which assumed vast “deforested” areas in wildland fires, a bias created by small plot size. We found higher conifer regeneration closer to live-tree edges, but we consistently found natural post-fire conifer regeneration at all distances into interior spaces of large high-severity fire patches, including >300 m from the nearest live trees. Distance from live-tree edges did not affect pine dominance in post-fire regeneration. The post-fire natural conifer regeneration reported in our results suggest that the adverse effects of current post-fire management in spotted owl habitat are not necessary practices that can be justified.